The “Happy Bouncing Ball” Game For The Learning of Table Tennis For Grade V Primary School Students "Permainan “Happy Bouncing Ball - Abdulaziz, Moch Fahmi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
Physical education, health and sports is an integral part of the overall education, aiming to develop physical fitness, skills of motion, critical thinking skills, social skills, reasoning, emotional stability, moral action, aspects of healthy living patterns and the introduction of clean environment through physical activity, sport and health selected planned systematically in order to achieve the goals of national education. Physical education, health and sports are the attempts to embody the whole person in the school, either from a basic to intermediate education level.Table tennis is one of the Physical education learning material taught in elementary school. However, the reality in the learning process has not been implemented optimally because the table was not proportional to the number of students. Thus the need to win and the modifications to the game, make students more actively in learning. The problems that plagued the school made teacher’s creativity in developing models of learning a new, yet fun and in accordance with the objectives of the learning that has been set. Modification of the learning game of ping-pong was one of the efforts that must be realized. Learning the ping-pong game through the happy bouncing ball game was expected to make children more actively engaged in a variety of pleasant situations and conditions, while following the learning of table tennis game.